Application of the Public Space Concept in the Strategic Development of the Master Plan for the Integrated International Islamic University of Indonesia in Depok, West Java - Ahmad Migdad Alaydrus; James E.D Rilatupa; Yophie Septiady (CV. Publikasi Indonesia, 2025)
University activities play a significant role in land use change, driving economic growth, and shaping neighborhood structure. This research aims to analyze the application of the public space concept in the strategic development of the master plan of Universitas Islam Internasional Indonesia (UIII). This research uses a literature study method and a combination of quantitative and qualitative approaches. Data were collected through site analysis, design concept, zoning, and sustainability management. The results show that the application of public space in UIII emphasizes the principles of sustainability, connectedness, and social functions to support academic, cultural, and religious activities. The discussion includes elements of green open space, environmentally friendly mobility, and integration of buildings with natural landscapes that create a comfortable and aesthetic environment. This research concludes that the development of public spaces in UIII successfully reflects the values of sustainability, social connectedness, and Islamic identity that support the university's function as a center of global civilization.